2023
DOI: 10.1038/s41598-022-21298-x
|View full text |Cite
|
Sign up to set email alerts
|

Imperatorin exerts antioxidant effects in vascular dementia via the Nrf2 signaling pathway

Abstract: Imperatorin, an active ingredient extracted from Angelica and Qianghuo, has anti-inflammatory, anti-oxidative stress damage, blocking calcium channels, and other properties. Our preliminary findings revealed the protective role of imperatorin in the treatment of vascular dementia, we further explored the underlying mechanisms concerning the neuroprotection function of imperatorin in vascular dementia. The cobalt chloride (COCl2)-induced chemical hypoxia and hypoglycemia of hippocampal neuronal cells was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Supplementation with phenolic acid, tannic acid, decreased liver iron, MDA and ROS levels [ 41 ]. Natural compounds including phenolic acids exhibit not only a direct antioxidant mechanism by removing ROS but may also impact an endogenous protective mechanism such as the Nrf2 defense signaling pathway [ 42 ]. Nrf2 is the central regulator involved in maintaining cellular redox homeostasis and modulating the expression of phase II enzymes such as NQO1, GCLC, GPX4 and HO-1, which in turn protect cells from oxidative damage, inflammation, and apoptosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with phenolic acid, tannic acid, decreased liver iron, MDA and ROS levels [ 41 ]. Natural compounds including phenolic acids exhibit not only a direct antioxidant mechanism by removing ROS but may also impact an endogenous protective mechanism such as the Nrf2 defense signaling pathway [ 42 ]. Nrf2 is the central regulator involved in maintaining cellular redox homeostasis and modulating the expression of phase II enzymes such as NQO1, GCLC, GPX4 and HO-1, which in turn protect cells from oxidative damage, inflammation, and apoptosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We wish to point out that published work has demonstrated that imperatorin exhibits low general toxicity [29]. For instance, imperatorin demonstrated minimal toxicity, with over 80% cell viability observed at concentrations up to 100 μM in normal hippocampal neuronal cells [32] and up to 50 μM in mouse bone-marrow-derived mast cells [51]. In our present investigation, we assessed the cytotoxicity of imperatorin in human embryonic kidney (HEK293) cells, a widely employed mammalian expression system.…”
Section: Imperatorin Reverses Abcg2-mediated Multidrug Resistance In ...mentioning
confidence: 98%
“…Imperatorin, a natural coumarin compound [24], can be isolated from various sources such as Notopterygium incisum (also referred to as Hansenia weberbaueriana) [25], Rhodiola bupleuroides [26], Foeniculum vulgare Mill [27], and Angelica dahurica [28]. Extensive research has detailed the pharmacological effects of imperatorin [29], encompassing its antibacterial [30], antiviral [31], antioxidant [32], antihypertensive [33,34], anti-inflammatory [35,36], hepatoprotective [37], and neuroprotective [38,39] properties. In addition, imperatorin has exhibited inhibitory effects on cell proliferation in a range of cancer types [40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…This condition promotes free radical formation, causing mitochondrial dysfunction, inducing white matter abnormalities, and increasing blood brain barrier permeability [ 8 , 9 ]. Emerging evidence suggests that oxidative stress also plays an important role in the pathogenesis of VaD [ 10 , 11 ]. Activated microglia in VaD can generate excessive reactive oxygen species (ROS), which can initiate oxidative stress and lead to neuronal damage and apoptosis, thus resulting in neuropathological changes and brain tissue injury and, ultimately, cognitive decline and behavioural dysfunction [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%